Pengaruh Net Profit Margin, Total Asset Turnover dan Debt to Equity Ratio terhadap Pertumbuhan Laba dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Perusahaan Food and Beverage di Bursa Efek Indonesia Periode 2016-2020 - Fatimah Zahara; Kersna Minan; Rizki Fillhayati Rambe (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the net profit margin, total asset turnover and debt to equity ratio on profit growth whether company size moderates the effect of net profit margin. on profit growth in Food & Beverage companies listed on the Indonesia Stock Exchange 2016-2020. The total population in this study were 30 companies and the sample in this study was 18 companies with 5 years of research anda total of 90 data were obtained. The analysis technique used is Moderated Regression Analysis (MRA). The results show that net profit margin does not affect profit growth, total asset turnover affects profit growth, debt to equity ratio affects profit growth, company size affects profit growth, company size does not moderate the effect between net profit margin and profit growth, firm size does not moderate the effect of total asset turnover with profit growth and firm size does not moderate the effect of debt to equity ratio with profit growth